Ovulation: endocrine and paracrine control of ovulation - Duffy, Diane M. (Henry Stewart Talks, 2021)
Endocrine and paracrine control of ovulation, Feedback control of ovulation, Endocrine versus paracrine control of ovulation, Progesterone, Prostaglandins and human ovulation